Endometrial Adenocarcinomas With Significant Mucinous Differentiation: A Characterization of Intratumoral Heterogeneity of KRAS Mutations in Mucinous and Endometrioid Histologic Components. Issue 2 (1st February 2018) - Jackson, Cynthia L.; Hang, Steven; Hansen, Katrine; He, Mai; Sung, C. James; Quddus, M. Ruhul; Xiong, Michelle; Wang, Yihong; Patel, Nimesh R.; Lawrence, W. Dwayne; Xiong, Jinjun
Abstract : Objective: KRAS mutations are frequently seen in malignancies with mucinous morphology. In our previous study, mucinous endometrial carcinomas were associated with a significantly higher frequency of KRAS mutations as compared with matched conventional endometrioid carcinomas.1 This study expands our previous report by exploring possible intratumoral heterogeneity for KRAS gene mutations in the mucinous components of mucinous carcinomas (MCs) and endometrioid carcinomas with significant mucinous differentiation (ECSMD) versus their associated "usual" endometrioid components. Materials and Methods: KRAS -positive cases from our previous report were studied, including 10 MCs and 10 ECSMDs. The specimens were microscopically dissected to separately isolate morphologically mucinous and endometrioid components. Direct DNA sequencing for KRAS mutations at codons 12 and 13 using capillary electrophoresis were performed. Results: KRAS mutations were detected in the endometrioid components of 8 (80%) of 10 MCs and 3 (30%) of 10 ECSMDs. The endometrioid component of the ECSMD group was less frequently associated with KRAS mutation than the endometrioid component of the MC group, even when the mucinous component of the same tumor contained a mutation; the difference is statistically significant ( P < 0.05). Conclusions: Our current study shows that intratumoral heterogeneity for KRAS gene mutation was associated with ECSMD, but less frequently with MC. It is possible that when the mucinous component predominates, qualifying for an MC, KRAS mutations appear to be widespread, irrespective of the mucinous or nonmucinous differentiation of the tumor cells. The findings suggest that multiple samples for KRAS tests may be useful, especially in endometrioid carcinoma with significant mucinous differentiation.